PENERAPAN MODEL JIGSAW PADA MATERI PERISTIWA KEBANGSAAN MASA PENJAJAHAN EROPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD NEGERI 2 TIJUE PERCONTOHAN - Abdul Manaf; Zahrina (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
The purpose of this study was to determine the activities of teachers and students in teaching and learning activities by applying the Jigsaw model to the material on National Events of the European Colonial Period in social studies learning and to improve the learning outcomes of fifth grade students at SDN 2 Tijue Pilot. The type of research conducted is classroom action research (CAR). The research subjects were the fifth grade students of SDN 2 Tijue Pilot, totaling 23 students. The data collection technique used in this research is to describe the learning experience with the application of cooperative methods and consider input from the observer to make changes or improvements to the weaknesses experienced by the research teacher in each cycle. The results showed that in the first cycle the average value was 62.2 with 43.5% classical completeness, the finding of weakness was that very few students were actively involved in learning activities, so improvements were made by applying the Jigsaw cooperative model in the second cycle. Cycle II uses the Jigsaw model with the average score increasing to 70.9 with classical completeness 78.3%, the finding of weakness in the second cycle is that there are still students who are passive in learning. Cycle III using the Jigsaw model increased again by obtaining an average value of 81.7 with 100% classical completeness, so learning was stopped in cycle III.